Assessment of kenaf as material for laminated woven kenaf/carbon fibre epoxy hybrid composites - Alias, Aisyah Humaira (2019)
Natural fibers received much attention as a reinforcement material in polymer composite, due to the environmental concerns by substituting synthetic fibres. Natural fibre reinforced composite (NFRC) is a composite material made up of a polymer matrix mixed with natural fibres, including kenaf fibre. However, the performance of the NFRC is still not comparable with synthetic polymeric composite. Therefore, hybridisation of natural fibres with synthetic fibre is suggested to produce biodegradable composite. Some researchers have found that natural fibres in woven fabric form produced better composite properties due to fabric structure. In this study, a three-layer laminated hybrid composites was produced from woven kenaf (Hibiscus cannabinus) fabric and carbon fibre by using epoxy as a matrix. Each composite consists of a single ply woven kenaf at the center layer and carbon fibres fabric at the upper and lower layers. The ratio of fabrics and resin was 30:70 by mass. The study was divided into three main parts: (i) evaluation of yarn properties, (ii) characterisation of woven kenaf fabric, and (iii) development of lamination woven kenaf/carbon fibre epoxy hybrid composite. Analysis on the yarn properties, the morphological characteristics, and mechanical properties on four types of yarn at different linear densities were studied. It was found that yarn with high linear density contains more amount of fibres, wider in yarn diameter, and higher in moisture content. The tensile strength and elongation of kenaf yarn increased, but the Young’s modulus reduced as the number of linear density increased. The production of woven fabric used two main parameters i.e., yarn linear density (500, 1000, 1500, and 2000 tex) and weave design (plain, satin, and twill). A total of 12 types of woven fabric were tested for basic properties and mechanical strength. The results show that the properties of woven kenaf fabric are more affected by yarn linear density compared to the weave design which appears to be contributed by the yarn size and properties. The crimp percentage and number of cross yarn were found to be the two major factors influencing the properties of the woven fabric. Fabric having 500 tex yarn with plain and satin design were found to have good fabric properties, thus were selected in the subsequent composite production. The physical properties (density, volume fraction, and void content), mechanical properties (tensile, flexural, and impact), thermal (TGA and DSC) and morphological properties of different weave designs i.e., plain and satin composites was studied. The effects of different fabric count (5 × 5 and 6 × 6) and the presence of carbon fibre were also studied. The three-layer hybrid composites were prepared by using vacuum impregnated process in the presence of epoxy resin. The result found that the effect of weave design on the composites properties is more prominent than that of fabric count. Significantly higher of tensile and impact properties were given by composite with plain fabric. Composite made from kenaf satin fabric, however had good flexural properties. Apparently, composite made from plain design kenaf fabric had better adhesion between the fibres and matrix, consequently gives significantly higher strength. However, by using 5 × 5 fabric count improved the flexural modulus, while fabric count of 6 × 6 improved the tensile and impact strengths. Such improvements may be attributed by the high fibre content and good fabric structure. The thermal stability of the laminated hybrid composites was slightly inferior to 100% carbon fibre composite, with the thermal stability of plain fabric composite was better than the satin fabric composite. The addition of carbon fibre in the NFRC has improved the TGA properties of hybrid composite. The overall results indicated that the hybridisation of woven fabric and carbon fibre had successfully enhanced mechanical properties of the composite. The hybrid composite properties found significantly affected by the yarn and fabric parameters.